(untitled) (International Journal of Engineering and Computer Science, 2017)
In our day today life quiz competition is rapidly increasing. So to get the appropriate results Fastest finger first (FFF) is used to know the players respond time. It is rapidly used in institute level as well as commercial level. In early days it is very tedious work to know who has buzzer the alarm first in fastest finger first. So the solution for this problem is to use PIC microcontroller 16F877A. This project is designed as a product based. Also it has a vast impact on industrial level for security purpose